Applying fuzzy theory concepts to the analysis of employment diversification of farm households: methodological considerations - Jana Fritzsch (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2008)
The Deliverable 7.2 (D7.2) of the SCARLED project provides methodological considerations for applying fuzzy set theory to the analysis of employment diversification of farm households. It presents a Mamdani's type fuzzy inference model and describes its application within the project's framework. The model consists of ten variables that are grouped into the four factors: (i) necessity to diversify, (ii) internal preconditions, (iii) external preconditions, and (iv) attitudes. The coherence of these four factors with the integrated framework for the analysis of nonfarm rural employment is discussed. The model will be realised in the Fuzzy Logic Toolbox from MATLAB®. Forty four membership functions and 138 rules are going to be implemented, tested, and adapted with survey data from the five countries: Bulgaria, Hungary, Poland, Romania, and Slovenia. The final model will be used to assess the diversification potential of 15 regions in these countries.
urn:nbn:de:gbv:3:2-11409
Keywords: 330